FT-Raman methodology applied to identify different ageing stages of wine spirits. (December 2020) - Anjos, Ofélia; Caldeira, Ilda; Pedro, Soraia Inês; Canas, Sara
Abstract: During the ageing process of wine spirits several phenomena occur, which are responsible for the final quality of the beverage. This work aimed to discriminate the aged wine spirits according to the wood species, ageing technology and ageing time using FT-Raman methodology. For this purpose, the same Lourinhã wine distillate aged in 250-L wooden barrels of Limousin oak wood (L) and chestnut wood (C) separately and used together (L + C), was monitored through FT-Raman during the first 12 months of ageing. This technique was also applied to the same wine distillate aged in stainless steel tanks with staves of the same kinds of wood and during the same period. FT-Raman allows separating the wine spirits according to the different wood species and ageing time. This technique seems to be a promising tool to monitor the ageing process of wine spirit through different technologies. Highlights: FT-Raman methodology towards monitoring different wine spirit ageing technologies. Differentiation of wood raw materials, ageing time and ageing technologies by FT-RAMAN. New ageing technologies with micro-oxygenation could be identified by FT-RAMAN.